ПРОСТРАНСТВЕННО-ВРЕМЕННОЕ МОДЕЛИРОВАНИЕ РИСКА ПЕРЕДАЧИ ВИРУСА БЛЮТАНГА В КАЗАХСТАНЕ - А. Жакенова; С. Абдрахманов (Animal Health and Biosafety, 2026)
Bluetongue (BT) is a transmissible viral infection affecting both domestic and wild ruminants, with high veterinary and economic significance. The pathogen is bluetongue virus (BTV), transmitted primarily by bloodsucking midges of the genus Culicoides. The spread of the disease is directly dependent on climatic, environmental, and biological conditions, which determine the population dynamics, activity, and viability of the vectors. Although no cases have been officially recorded in Kazakhstan in recent years, serological data indicate possible circulation of the virus in susceptible animal populations. This necessitates assessing the spatiotemporal risks of infection. The primary objective of this study was to assess the seasonal and geographic risk factors for bluetongue transmission in the Republic of Kazakhstan using mathematical modeling based on the basic reproduction number (R₀). The initial data included cattle and small cattle population statistics for 2,466 rural districts across the country, as well as long-term climate data. The model took into account animal density, vector abundance, temperature-dependent vector survival, infection rate, precipitation, and other environmental parameters. Spatial analysis and visualization of the results were implemented in the R software environment using geoinformation technologies. Analysis of the modeling data revealed clear spatial and temporal differentiation in the likelihood of bluetongue virus spread. The period from October to March is characterized by a low risk of infection transmission. In the spring, risk hotspots develop primarily in southern Kazakhstan, after which the affected area gradually shifts north. The peak epidemiological danger is recorded in July in the northern and northeastern regions. These findings serve as the basis for optimizing epidemiological monitoring, planning vaccination, and strengthening preventive measures.